Systematic Review: Does Pre-Pubertal Spaying Reduce the Risk of Canine Mammary Tumours? - Phillip Guirguis; David S. Beggs (Animals, 2025)
Background: Ovariectomy and ovariohysterectomy (spaying) are two surgical procedures commonly performed on dogs. However, the optimum age at which to perform these procedures in dogs remains a contentious issue. Following work published in the 1960s, pre-pubertal spaying became popular largely on the basis that it reduced the risk of mammary cancer development. However, a systematic review published more than 10 years ago questioned this. The objective of this study was to examine the strength and direction of updated literature on the relationship between spaying age of dogs and mammary tumour development and to investigate whether the evidence has changed. Method: A systematic review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. In March 2023, peer-reviewed articles were collected from three databases (CAB direct, Web of Science, and PubMed). Articles were excluded if they were not in English, not peer-reviewed, not relevant to PICO (Population, Intervention, Comparison and Outcome), or if the study investigated the effects of desexing on canines with mammary tumours already or of the prognosis and not development of mammary tumours. Results: Of 232 articles obtained from the initial database search, 13 articles were found to meet the inclusion criteria. Six out of the thirteen papers selected found no evidence of a protective effect of early spaying against mammary tumour development. Conclusion: This review suggests that further breed-specific studies with matched controls on the main risk factors would help address issues such as lack of appropriate statistical analysis, control of biases, and confounding risk factors. The benefits of early spaying should be balanced with other considerations about the optimal age for spaying dogs.